Implementasi Nilai-Nilai Kebangsaan Bersumber UUD 1945 dan NKRI Guna Membangun Pertahanan Digital yang Kuat: Pentingnya Manajemen Sekuriti dalam Menghadapi Cybercrime - Dhini Dwi Aprilia; Edy Soesanto; Diah Sekar Arum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In an era of rapid digital transformation, Indonesia faces major challenges in ensuring security, privacy and compliance are maintained. With increasing cyber threats in the country, BSSN and the Government must be more careful about potential large-scale security breaches and must prioritize building strong defense mechanisms to protect Indonesia's digital assets. Therefore, Cyber Security is the main pillar for the progress and sustainability of Indonesia's digital transformation. Then, legal provisions were issued in the form of Criminal Code Legislation and ITE Law no. 11 of 2008. The research method used in writing this article uses a qualitative method with a literature study approach. This research aims to provide an explanation regarding the compilation of national values originating from the 1945 Indonesian Constitution (UUD 1945) and the Unitary State of the Republic of Indonesia (NKRI) regarding security management. Specifically, this research examines the role of security management in dealing with cybercrime and strengthening digital defenses. It is hoped that the results of this research can be used as a reference for further research in increasing readers' insight and knowledge regarding the theme of this article.